Protocol relating to the Madrid Agreement concerning the international registration of marks : adopted at Madrid on June 27, 1989, as amended on October 3, 2006, and on November 12, 2007; regulations under the protocol relating to the Madrid Agreement concerning the international registration of marks as in force on February 1, 2023; administrative instructions for the application of the protocol relating to the Madrid Agreement concerning the international registration of marks as in force February 1, 2023; schedule of fees as in force February 1, 2023 (World Intellectual Property Organization, 2023)
The present publication contains the texts of the Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks (hereinafter referred to as the "Protocol") (1989), as amended in 2006 and in 2007, the Regulations under the Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks, the Administrative Instructions for the Application of the Protocol and the Schedule of Fees.